Emergence of ceftazidime/avibactam resistance in KPC-8–producing Klebsiella pneumoniae in South America - García, J. (2020)
Klebsiella pneumoniae is one of the so-called ESKAPE pathogens. These organisms are the main cause of nosocomial infections worldwide, causing life-threatening infections amongst critically ill and immunocompromised individuals. They are characterized by drug resistance mechanisms. Klebsiella pneumoniae carbapenemase (KPC)-producing isolates display resistance to multiple antimicrobial agents, usually including last-resort alternative options, leading to an urgent need to develop new drugs or combinations. In Argentina sequence type (ST) 258 harbouring bla KPC-2 emerged in 2010 and remained prevalent until the last few years, when the emergence of different STs such as ST25, ST11 and ST307 appeared likely to change the local epidemiology.